Neutron stars in a class of nonlinear relativistic models - Taurines, Andre Ribeiro (2014)
In this work we introduce a class of relativistic models for nuclear matter and neutron stars which exhibits a parametrization, through mathematical constants, of the nonlinear meson-baryon couplings. For appropriate choices of the parameters, it recovers current quantum hadrodynamics models found in the literature: the Walecka model and Zimanyi-Moszkowski models (ZM and ZM3). For other choices of parameters, the models give very interesting and new physical results. The phenomenology of neutron stars in ZM models is presented and compared to the phenomenology obtained in other versions of the Walecka model. We have found that the ZM3 model is too soft, and predicts a very small maximum neutron star mass, ~0.72Mʘ. A strong similarity between the results of ZM-like models and those with exponential couplings is noted. The sensibility of the results to the specific choice of the values for the binding energy and saturation density is pointed out. Finally, we discuss the very intense scalar condensates found in the interior of neutron stars, which may lead to negative effective masses.